Evaluation of the Quality of Additional Employee Income using the McCall Method - Syafni Yolandari; Sri Rahmawati; Mardison (Journal of Computer Scine and Information Technology, 2024)
The use of information technology is a basic need for an organization. Additional Quality of Employee Income ( TPP ) in an agency is very important as a medium for conveying information in every employee activity at the Padang Panjang PUPR Service Office. The quality of the TPP will be known after an evaluation is carried out. The quality of the TPP is included in the good or bad category. TPP quality testing is an important thing to determine the quality of human resources . One way to test quality is to use the McCall method . The McCall method is a method for measuring the quality of TPP implemented at the Padang Panjang PUPR Service Office. This research was carried out by filling out a questionnaire using the PHPMySQL programming language using the McCall method. This evaluation activity is used to measure the attitudes, opinions and perceptions of a person or group of people about an event. The results of this research also show that the results of the evaluation carried out produced a percentage on a scale of 81% - 100% = 84% and were categorized as Good. By carrying out this quality evaluation.